Beyond the interviews: enabling employers to preview your capabilities - Sutton, Kyra Leigh (Henry Stewart Talks, 2021)
Work samples and portfolios, What work samples are, Kinds of work samples, The relevance of having a portfolio, How to build your candidate’s portfolio, What to include and what to not include in your portfolio